Integration of Absolute Assignment in the Takaful Industry and its Implications on Islamic Estate Planning - Abdullah, Muhamad Muizz; Mohd Arif, Mohd Izzat Amsyar; Abd Manaf, Aiman Amalina; Sabri, Muhammad Farid (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
One of the important aspects of takaful is the use of Absolute Assignment which allows the transfer of full ownership of takaful benefits to the trustee. However, the implementation of the Absolute Assignment in the context of Islamic estate planning‎ is still unclear and will affect to the inheritance conflicts. Therefore, this study will analyze the extent to which the integration of the Absolute Assignment can be implemented in the Islamic estate planning industry, especially involving the appointment of trust institutions as a trustee. This study is qualitative by using the content analysis method on journal articles, books, acts and court cases. Interview were also conducted with representatives of two trust institutions in Malaysia, namely Amanah Raya Berhad (ARB) and as-Salihin Trustee Berhad, to find out about estate planning products that use Absolute Assignment. In addition, an interview was also conducted with a takaful practitioner from Takaful Ikhlas company to learn more about the implementation of the Absolute Assignment. In conclusion, this study found that there are four main implications through the integration of Absolute Assignment in the takaful industry, namely speeding up the estate administration process, helping to ease the cost burden, safeguarding the welfare of beneficiaries and free tax of takaful benefit. This study suggests that an active collaboration should be implemented between takaful companies and trust institutions in Malaysia to produce variations of takaful products based on Islamic estate planning.